Web-based education : concepts, methodologies, tools and applications - Information Resources Management Association (Hershey, Penn. : Information Science Reference, 2010)
'This comprehensive collection offers a compendium of research on the design, implementation, and evaluation of online learning technologies, addressing the challenges and opportunities associated with the creation and management of Web-based applications and communities, instructional design, personalized learning environments, and effective educational delivery'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Web-based instruction; Computer-assisted instruction